Mental health resilience in the adolescent offspring of parents with depression: a prospective longitudinal study. (January 2016) - Collishaw, Stephan; Hammerton, Gemma; Mahedy, Liam; Sellers, Ruth; Owen, Michael J; Craddock, Nicholas; Thapar, Ajay K; Harold, Gordon T; Rice, Frances; Thapar, Anita
Summary: Background: Young people whose parents have depression have a greatly increased risk of developing a psychiatric disorder, but poor outcomes are not inevitable. Identification of the contributors to mental health resilience in young people at high familial risk is an internationally recognised priority. Our objectives were to identify protective factors that predict sustained good mental health in adolescents with a parent with depression and to test whether these contribute beyond what is explained by parent illness severity. Methods: The Early Prediction of Adolescent Depression study (EPAD) is a prospective longitudinal study of offspring of parents with recurrent depression. Parents with recurrent major depressive disorder, co-parents, and offspring (aged 9–17 years at baseline) were assessed three times over 4 years in a community setting. Offspring outcomes were operationalised as absence of mental health disorder, subthreshold symptoms, or suicidality on all three study occasions (sustained good mental health); and better than expected mental health (mood and behavioural symptoms at follow-up lower than predicted given severity of parental depression). Family, social, cognitive, and health behaviour predictor variables were assessed using interview and questionnaire measures. Findings: Between February and June, 2007, we screened 337 families at baseline, of which 331 were eligible. Of these, 262 completed the three assessments and were included in the data for sustained mental health. Adolescent mental health problems were common, but 53 (20%) of the 262 adolescents showed sustained good mental health. Index parent positive expressed emotion (odds ratio 1·91 [95% CI 1·31–2·79]; p=0·001), co-parent support (1·90 [1·38–2·62]; p<0·0001), good-quality social relationships (2·07 [1·35–3·18]; p=0·001), self-efficacy (1·49 [1·05–2·11]; p=0·03), and frequent exercise (2·96 [1·26–6·92]; p=0·01) were associated with sustained good mental health. Analyses accounting for parent depression severity were consistent, but frequent exercise only predicted better than expected mood-related mental health (β=–0·22; p=0·0004) not behavioural mental health, whereas index parents' expression of positive emotions predicted better than expected behavioural mental health (β=–0·16; p=0·01) not mood-related mental health. Multiple protective factors were required for offspring to be free of mental health problems (zero or one protective factor, 4% sustained good mental health; two protective factors, 10%; three protective factors, 13%, four protective factors, 38%; five protective factors, 48%). Interpretation: Adolescent mental health problems are common, but not inevitable, even when parental depression is severe and recurrent. These findings suggest that prevention programmes will need to enhance multiple protective factors across different domains of functioning. Funding: Sir Jules Thorn Charitable Trust, Economic and Social Research Council.